"Gulf Security is Our Security": Global Britain and UK Gulf Strategy, 2010-20. Issue 2 (3rd April 2021) - Devanny, Joe; Berry, Philip
ABSTRACT: "Global Britain" has become the framing concept for post-Brexit foreign policy pursued by successive Conservative prime ministers. Despite exaggerated rhetoric to the contrary, this has not led to a significant shift in Britain's Gulf strategy, but rather intensified the pursuit of the existing network of bilateral relationships underpinned by security cooperation, defence exports and inward investment. A modest uplift of UK military presence in the Gulf has not demonstrably increased UK influence in the region or over the regional decisions of the Trump administration. This leaves the UK more exposed to risk from deteriorating relations between the US and Iran. It also highlights the delicate balance between Britain's increasing focus on pursuing domestic economic objectives and its modest defence, diplomatic and security contribution to stability in the Gulf. As Saudi Arabia and the UAE pursue increasingly active and independent regional policies, the UK must reappraise commitments implicit in its interdependent trade- and security-focused strategy to prepare for the possibility of difficult choices, both between allies and about the nature of UK involvement in future regional conflicts.